1996
DOI: 10.1093/oxfordjournals.eurheartj.a015005
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of repolarization following double and triple programmed stimulation: A clinical study using the monophasic action potential recording technique

Abstract: To study the dispersion of ventricular repolarization following double and triple programmed stimulation and its correlation with the inducibility of ventricular arrhythmias, monophasic action potentials were simultaneously recorded from the right ventricular apex and outflow tract during programmed stimulation in 12 patients with ventricular arrhythmias and a normal QT interval. The time difference between the ends of the two monophasic action potentials were used as a measure of the dispersion of ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…In the present study, not only the QTd-VPB was significantly greater than QTd-SB, but an even more significant difference was present between QTd-SB and QTd-Vpace. These results show that regional variation in ventricular recovery is more increased following ventricular extrasystoles than during sinus beats and confirm the results of other studies 10,12,13 that have shown that one of the triggering mechanisms of VPBs in sustained VT induction may be a further increase in nonuniformity of repolarization. patients) might have also accounted for these differences.…”
Section: Qtd Values Obtained Using Three Different Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, not only the QTd-VPB was significantly greater than QTd-SB, but an even more significant difference was present between QTd-SB and QTd-Vpace. These results show that regional variation in ventricular recovery is more increased following ventricular extrasystoles than during sinus beats and confirm the results of other studies 10,12,13 that have shown that one of the triggering mechanisms of VPBs in sustained VT induction may be a further increase in nonuniformity of repolarization. patients) might have also accounted for these differences.…”
Section: Qtd Values Obtained Using Three Different Methodssupporting
confidence: 91%
“…We have demonstrated that the shorter the coupling interval of a paced ventricular beat, the greater the QTd. These findings are in agreement with the results of Yuan et al 12 who, using monophasic action potential recordings from two ventricular sites, demonstrated the maximal dispersion of ventricular repolarization occurring 10-20 ms before the ventricular effective refractory period in 11 of the 12 patients studied.…”
Section: Effects Of Vpb On Qtdsupporting
confidence: 93%
See 1 more Smart Citation
“…Human ventricular wall comprises three electrophysiologically and functionally distinct cell types: epicardial, mid‐myocardial and endocardial cells, with M cells showing the longest action potential (AP) duration; the intrinsic differences in AP duration lead to a transmural repolarisation heterogeneity among the layers . In pathological conditions, transmural electrical differences in APs are amplified, with the consequent higher dispersion of repolarisation across the ventricular wall and the increased vulnerability to ventricular arrhythmias …”
Section: Introductionmentioning
confidence: 99%
“…1 In pathological conditions, transmural electrical differences in APs are amplified, with the consequent higher dispersion of repolarisation across the ventricular wall and the increased vulnerability to ventricular arrhythmias. 2 Dispersion of ventricular repolarisation (DVR) can be assessed non-invasively using a 12-lead surface electrocardiogram (ECG). It has, in fact, been demonstrated, by means of monophasic action potentials recordings, that some electrocardiographic variables involving the terminal part of QT, such as the Tpeak-Tend (Tpe) interval, reflect indirectly DVR.…”
Section: Introductionmentioning
confidence: 99%